Phylogeographic Analysis and Genetic Structure of an Endemic Sino-Japanese Disjunctive Genus Diabelia (Caprifoliaceae) - Zhao, Kun-Kun; Landrein, Sven; Barrett, Russell L.; Sakaguchi, Shota; Maki, Masayuki; Mu, Wei-Xue; Yang, Ting; Zhu, Zhi-Xin; Liu, Huan; Wang, Hua-Feng (Frontiers in Plant Science, 2019)
The Sino-Japanese Floristic Region (SJFR) is a key area for plant phylogeographical research, due to its very high species diversity and disjunct distributions of a large number of species and genera. At present, the root cause and temporal origin of the discontinuous distribution of many plants in the Sino-Japanese flora are still unclear. Diabelia (Caprifoliaceae; Linnaeoideae) is a genus endemic to Asia, mostly in Japan, but two recent discoveries in China raised questions over the role of the East China Sea (ECS) in these species' disjunctions. Chloroplast DNA sequence data were generated from 402 population samples for two regions (rpl32-trnL, and trnH-psbA) and 11 nuclear microsatellite loci were screened for 549 individuals. Haplotype, population-level structure, combined analyses of ecological niche modeling, and reconstruction of ancestral state in phylogenies were also performed. During the Last Glacial Maximum (LGM) period after the Tertiary, Diabelia was potentially widely distributed in southeastern China, the continental shelf of the East China Sea and Japan (excluding Hokkaido). After LGM, all populations in China have disappeared except those in Zhejiang which may represent a Glacial refuge. Populations of Diabelia in Japan have not experienced significant bottleneck effects, and populations have maintained a relatively stable state. The observed discontinuous distribution of Diabelia species between China and Japan are interpreted as the result of relatively ancient divergence. The phylogenetic tree of chloroplast fragments shows the characteristics of multi-origin evolution (except for D. sanguinea). STRUCTURE analysis of nuclear Simple Sequence Repeat (nSSR) showed that the plants of the Diabelia were divided into five gene pools: D. serrata, D. spathulata, D. sanguinea, D. ionostachya (D. spathulata var. spathulata-Korea), and populations of D. ionostachya var. ionostachya in Yamagata prefecture, northern Japan. Molecular evidence provides new insights of Diabelia into biogeography, a potential glacial refuge, and population-level genetic structure within species. In the process of species differentiation, ECS acts as a corridor for two-way migration of animals and plants between China and Japan during glacial maxima, providing the possibility of secondary contact for discontinuously distributed species between China and Japan, or as a filter (creating isolation) during glacial minima. The influence of the ECS in speciation and biogeography of Diabelia in the Tertiary remains unresolved in this study. Understanding origins, evolutionary histories, and speciation will provide a framework for the conservation and cultivation of Diabelia.